Evaluation of the impact of chemotherapy on eating habits of women with non-metastatic breast cancer - Braz, Katia Cristina Camondá; Mello, Celso Abdon Lopes; Fanelli, Marcello Ferretti; Chinen, Ludmilla Thomé Domingos (Brazilian Journal of Oncology, 2022)
Introduction: There are few studies that investigated the eating habits of patients with breast cancer undergoing chemotherapy.Objectives: To study the changes in dietary intake during chemotherapy, relating to sociodemographic variables, gastrointestinal side effects, and changes consumption in food groups.Material and Methods: This study was made at Clinical Oncology Department of A.C. Camargo Cancer Center, Sao Paulo, Brazil. We investigated weight, height and food intake as measured using the food frequency questionnaire (FFQ), before and after chemotherapy treatment alone with anthracyclines, with curative intent, for patients with non-metastatic breast cancer.Results: A total of 41 patients participated in the first phase of the study, and 26 completed the second phase. Milk and milk derivatives, beef stroganoff, liver, tuna and sardines, shrimp, papaya, fruit juices such as cashew, acerola (Barbados cherry, Malphighia punicifolia), vegetables with high fat content, and macaroni/pasta had increased consumption (p<0.05) during treatment. In contrast, lettuce and escarole were eaten less (p<0.05). Meat, fish, eggs, and sweets, savory snacks and decorated sweets with icing sugar were all subject to increased consumption (p<0.05). A loss of appetite was associated with meat, fish, and eggs; nausea was associated with bread, cereals, root vegetables and legumes consumption (p<0.05). These changes were not associated with an increase in body mass index, and there was no correlation with sociodemographic variables.Conclusion: Changes in patterns of food intake in patients on chemotherapy was found and deserve attention, as gain weight is related to disease relapse in breast cancer.
Keywords: Food; Chemotherapy; Adjuvant; Breast neoplasms; Diet; Feeding behavior; Nutritionists